INSTITUTIONAL ENVIRONMENT OF FEMALE ENTREPRENEURS IN KAZAKHSTAN (Journal of Economic Research & Business Administration, 2018)
Positive trend on the number of female entrepreneurs in Kazakhstan has been noticed in recentyears. Female entrepreneurs are provided with enormous opportunities in countries with transitionaleconomy including Kazakhstan. However, researches provided in developing countries and countrieswith transitional economies found out that female entrepreneurs are not provided with proper institutionalenvironments, and it serves as a significant problem for them in making a decision to start and/ormaintain the business. The barriers exist in the form of heavy tax rates, lack of finance, ineffective bankingsystem, traditional restricted social norms and values and ever-changing legal-system. The aim of thispaper was to explore the institutional environment of female entrepreneurs in Kazakhstan and identifyhow institutional environment influences women’s decision to start and/or maintain their businesses.This theoretical paper with secondary data analyzes investigates whether the institutional environment ofwomen is positively correlated with female entrepreneurial opportunities; and whether this opportunitypositively influenced the number of female entrepreneurs in Kazakhstan or not. In order to test thosetwo hypotheses, the researches put the objectives of, firstly, to review the existing literature concerningthe institutional environment of female entrepreneurs in Kazakhstan and countries with transitionaleconomies; secondly, to analyze the cases of institutions surrounding and influencing the operations offemale entrepreneurs in Kazakhstan; and, lastly, to compare the findings with the theoretical frameworkand make a decision to accept/reject the hypotheses.